2014
DOI: 10.1371/journal.pone.0106812
|View full text |Cite|
|
Sign up to set email alerts
|

Urotensin II Inhibits Doxorubicin-Induced Human Umbilical Vein Endothelial Cell Death by Modulating ATF Expression and via the ERK and Akt Pathway

Abstract: Background and PurposeRegulation of the homeostasis of vascular endothelium is critical for the processes of vascular remodeling and angiogenesis under physiological and pathological conditions. Urotensin II (U-II), a potent vasoactive peptide, participates in vascular and myocardial remodeling after injury. We investigated the protective effect of U-II on doxorubicin (DOX)-induced apoptosis in cultured human umbilical vein endothelial cells (HUVECs) and the potential mechanisms involved in this process.Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
3
5
0
Order By: Relevance
“…In addition to cancer spheroids, the drug was also found to be cytotoxic to HUVECs cells as the endothelial barrier was found to have disappeared upon exposure to Doxorubicin. This finding is consistent with other reports, which showed the cytotoxic effect of Doxorubicin on endothelial cells 37 .…”
Section: Resultssupporting
confidence: 94%
“…In addition to cancer spheroids, the drug was also found to be cytotoxic to HUVECs cells as the endothelial barrier was found to have disappeared upon exposure to Doxorubicin. This finding is consistent with other reports, which showed the cytotoxic effect of Doxorubicin on endothelial cells 37 .…”
Section: Resultssupporting
confidence: 94%
“…Zhang et al (2022) also found that Ang II increased the proliferation and ferroptosis levels of cardiac microvascular endothelial cells at the same time. In addition, UII did not affect AF apoptosis (data not shown), which was consistent with the results of Chen et al (2014). Chen et al (2014) showed that UII did not affect the apoptosis of human umbilical vein endothelial cells, but inhibited doxorubicininduced cell apoptosis.…”
Section: Discussionsupporting
confidence: 87%
“…In line with the data on IL-1β, TNF-α, and thrombomodulin ( Figure 1 and Figures S1–S3 ), DENV and rEIII treatment induced endothelial cell death in a dose-dependent manner ( Figure 2A ). Overall, various cell death inducers, including doxorubicin (apoptosis) ( 36 , 37 ), rapamycin (autophagy) ( 38 ), erastin (ferroptosis) ( 39 ), TNF-α (necroptosis) ( 40 , 41 ), nigericin (pyroptosis) ( 42 ), served as positive control agents to induce respective cell death pathway of the tested endothelial cells ( Figures 2B, C , dead cell population adjusted to 100%; Figure S3 , flow cytometry gating and calculation). Notably, when compared with cell death agonists, DENV and rEIII treatment induced considerable pyroptosis, necroptosis, and ferroptosis responses in the endothelial cells, but only minor manifestations of apoptosis ( Figure 2B , % of total cells; 2C, % of total dead cell).…”
Section: Resultsmentioning
confidence: 99%